Dancing with Cuba : A Memoir of the Revolution - Guillermoprieto, Alma, 1949-; Translated from the Spanish by Allen, Esther, 1962- (New York Vintage Books, 2005)
Alma Guillermoprieto--an award-winning journalist and arguably our most clear-eyed observer of Latin America--now turns her keen powers of observation onto her own, younger self. In this richly evocative chronicle, Guillermoprieto describes the remarkable, transforming journey she made as a twenty-year-old, when her love of dance--which had led her from her native Mexico to the New York dance studios of Martha Graham, Merce Cunningham, and Twyla Tharp--took her to a job teaching poorly trained but ardent dance students in Cuba. At first unaffected by the revolutionary spirit and the adoration of Castro that pervaded the island, Guillermoprieto slowly fell under the spell of the idealism that buoyed the often destitute lives of the Cuban people. And as she opened herself to what became a complex, galvanizing revolutionary experience, she found, as well, the ideas and ideals that would shape her thinking for the rest of her life. Beautifully written and deeply felt, Dancing with Cuba is a revelatory account of the making of an impassioned political heart and mind.--Publisher description
Keywords: Travel -- Cuba -- Guillermoprieto, Alma, 1949-